Analisis Finansial Usaha Pembenihan Ikan Pada Kondisi Pandemi Covid-19 Di Desa Ponoragan Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - jeklin; Said Abdusysyahid; Juliani (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
The research objective is to determine the technical and management aspects, feasibility hatchery business, the difference in the income of cultivator in the conditons of the covid-19 pandeic and before the covid-19 pandemic, as well as knowing the obstacles and solutions fish hatchery business in Ponoragan Village. The research was carried out from September 2021 to March 2022 in Ponoragan Village, Loa Kulu District, Kutai Kartanegara Regency. A sample of 20 respondents with reference to the method purposive sampling. The results showed that the technical aspects consisted of pond preparation, selection of broodstock, spawning, stocking of larvae, rearing nener and harvesting seeds. The management functions used by hatchery cultivators are planning, implementation and monitoring management functions. Then, based on the criteria of BCR, NPV, IRR, BEP and Payback Period, it shows that the fish hatchery business in Ponoragan Village is feasible to run. The results of the T-test showed that there was a significant difference between the income of cultivators before and during the covid-19 pandemic, as well as the problems faced by hatchery cultivators, namely weather, pests and varieties. The solution is that farmers make fences from nets around the pond to prevent flooding, while for pests, farmers make snares from threads that are pulled on each side above the pond.